PATH ANALYSIS : DIRECT AND INDIRECT EFFECT HYPOTHESIS TESTING USING JACKKNIFE RESAMPLING ON THE DEVELOPMENT OF A CASHLESS SOCIETY - Dea Saraswati Pramaningrum (Parameter: Journal of Statistics, 2026)
This study investigates the direct and indirect effects of marketing mix variables, namely Product, Price, and Promotion, on the Development of a Cashless Society, with the Digitization of Electronic Money serving as a mediating variable. Path analysis was employed using secondary data obtained from a survey of 100 mobile banking users in Jakarta during the COVID-19 pandemic. To reduce dependence on distributional assumptions, hypothesis testing of the path coefficients was performed using the jackknife resampling method. The results indicate that Price and Promotion have significant positive direct effects on the Digitization of Electronic Money, while the Digitization of Electronic Money has a significant direct effect on the Development of a Cashless Society. Furthermore, Price and Promotion exert significant indirect effects on the development of a cashless society through the mediating role of electronic money digitization, whereas Product has neither a significant direct nor indirect effect. The proposed model achieved a Q-square predictive relevance of 0.5893, indicating moderate-to-high predictive capability. These findings highlight the critical role of electronic money digitization in facilitating the transition toward a cashless society and demonstrate that jackknife resampling provides a robust approach for hypothesis testing in path analysis when normality assumptions are questionable